Exploring beneath the retreating ice: swath bathymetry reveals sub- to proglacial processes and longevity of future alpine glacial lakes - Hosmann, Siro L.; Fabbri, Stefano C.; Büchi, Marius W.; Hilbe, Michael; Bauder, Andreas; Anselmetti, Flavio S. (Annals of Glaciology, 2024)
Knowledge of how glaciations formed landscapes is particularly important as receding glaciers currently uncover subglacial landscapes that are prone to a series of natural hazards, but that also bring opportunities for hydropower or water resources. We present high-resolution (1 × 1 m) swath bathymetric data of a proglacial lake in front of the Rhonegletscher (Swiss Alps) that started to form in the early 2000s allowing a look into a freshly uncovered glacier bed and its characterized morphology in an overdeepened setting. The comparison of two surveys from 2015 and 2021 allows an unprecedented quantification of the accumulation and erosion processes in the central lake basin. This highly dynamic environment is character- ized by iceberg calving, fluctuating outflow conduits, rapid sedimentation due to particle-laden meltwaters and dumped glacial debris. Assuming constant sediment yield, the Rhone Lake would persist for ∼300 years. However, as intense glacier retreat continues in the coming decades, a chain of overdeepened lakes will be revealed that will act as long persisting sediment traps.